Comparative assessment of energy-cum-carbon flow of diverse tillage production systems for cleaner and sustainable crop production in the middle Indo-Gangetic Plains of South Asia - Kumar, Abhay; Kumar, Rakesh; Sarkar, Sudip; Singh, Dhiraj Kumar; Kumar, Ujjwal; Sundaram, Prem Kumar; Kewal, Ram; Sainath, Banda; Raman, Rohan Kumar; Das, Anup; Kumar, Santosh; Mukherjee, Anirban; et al. (Frontiers in Sustainable Food Systems, 2025)
The most common cropping production system in South Asia, transplanted puddled rice followed by conventional-tillage wheat, is highly unsustainable, extremely energy-intensive, and emits a large amount of greenhouse gases. The practices used in conservation agriculture, including diversified cropping rotations, residue retention, zero-tillage direct-seeded rice, and zero-tillage wheat, can increase crop productivity while reducing energy use requirements and carbon footprints. Therefore, to promote a sustainable and energy-efficient conservation agriculture-based system with a less energy-intensive rice–wheat system, contrasting tillage and residue management scenarios were evaluated in this study. The treatments include triple cropping systems of zero-tillage direct-seeded rice (ZTDSR) during the rainy season, followed by zero-tillage rice–wheat–mungbean (ZTRWM) in winter, as well as zero-tillage rice–lentil–mungbean (ZTRLM), zero-tillage rice–chickpea–mungbean (ZTRCM), and zero-tillage rice–mungbean–mustard (ZTRMM) along with the conventional-tillage rice–wheat (CTRW) system. Zero-tillage systems exhibited significantly lower operational energy for irrigation ( 40%), sowing ( 26%), and land preparation (100%) compared to a conventional-tillage (CT) system. Compared to the conventional-tillage rice–wheat system, zero-tillage cropping systems achieved significantly higher system biomass yields. The zero-tillage system also increased wheat yields, resulting in a significant reduction in resources (fuel, fertilizer, and machinery) under zero-tillage (ZT) interventions. More than 60% of energy utilization came from crop residue, irrespective of the diverse cropping production systems. The maximum net energy returns, energy ratios, energy productivity, and energy intensity were recorded with the zero-tillage rice–wheat system. Zero-tillage production systems had significantly lower carbon footprints, higher carbon efficiency, and better carbon sustainability index than the conventional-tillage (CT) management system. Thus, it can be concluded that triple-zero-tillage production systems, along with residue management, yield lower net energy output, greenhouse gas emissions, and carbon footprints as compared to conventional-tillage-based systems.